Advances In Stable Mixed-Cation and Mixed-Halide Hybrid Perovskite Solar Cells : Toward High Efficiency and Long-Term Durability - Gulab Singh Verma,; Dr. Aloke Verma, (International Journal of Scientific Research in Science and Technology, 2025)
The rapid advancement of hybrid perovskite solar cells (PSCs) has transformed photovoltaic research. They have a great combination of high efficiency, low production costs, and materials that can be changed. But when exposed to heat, moisture, and UV light, single-cation and single-halide perovskites become unstable. Because of this instability, they can't be used on a large scale. Recent advances in mixed-cation and mixed-halide engineering offer a robust approach to address these challenges. This method makes the phases more stable, aligns the bands better, and stops ions from moving around. The structural tolerance factor and environmental stability have both improved a lot by using a mix of A-site cations like FA⁺, MA⁺, Cs⁺, and Rb⁺, along with halides like I⁻, Br⁻, and Cl⁻. Consequently, certain devices now attain efficiencies exceeding 25% and exhibit prolonged operational longevity. This review examines the mechanisms influencing stability and performance, synthesis techniques, and innovative designs in mixed-composition perovskites. It also talks about important strategies like additive-enhanced fabrication, protecting interfaces, and controlling compositional gradients. We talk about problems that are still going on, like how to increase production, make sure things can be done over and over again, and keep the environment safe. We also look at possible future options, such as 2D/3D hybrid systems and combining tandem technologies. The review ends by stressing how important the relationship between structure and stability is for making commercially viable, next-generation perovskite solar technologies.
Keywords: Mixed-Cation Perovskite; Mixed-Halide Perovskite; Stability; Bandgap Engineering; Interface Passivation; Photovoltaic Performance